Transovarial Transmission and Dengue Virus Serotypes in Aedes Aegypti In Kupang (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2016)
Dengue is an endemic disease in almost all provinces in Indonesia, including NTT pro-vince and Kupang City. DHF prevention and control efforts need to be accompanied by understanding of the epidemiological and entomological aspects. This study proves the presence of transovarial transmission and serotypes of Dengue virus in Ae. aegypti in areas with different endemics in Kupang City. The study was conducted in endemic, sporadic and Dengue-free villages. Samples from each location were 30 head squash Ae. aegypti females for examination of Dengue virus by IHC methods and 10 Ae. aegypti females for serotypes check of Dengue virus with RTPCR. Data presented in tables and images then analyzed descriptively. This study finds that transovarial infection rates 9.2% with serotype Dengue virus-1. As many 97.5% of respondents have heard about Dengue by most cadres resources (24.5%) and health workers (24%). Transovarial infection is found in endemic, sporadic and free areas so that the Dengue vector control needs to be done in the three regions with different endemicity.